Analisis Peran Pendidikan Jasmani terhadap Kepercayaan Diri dan Perkembangan Motorik Kasar Anak Sekolah Dasar - Maylani, Putri Intan; Setia Lengkana, Anggi; Nur Alif, Muhammad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the role of physical education on children's self-confidence and developing gross motor development. The design of this study is descriptive qualitative. The subjects involved in this study were grade VI students and teachers at one of the State Elementary Schools in Cimanggung District, Sumedang Regency. In this study, data collection techniques used observation, interview, and documentation techniques to see how the role of physical education affects children's self-confidence and gross motor development. The results of this study indicate that there are problems with teachers who do not provide understanding to children first so that in practice children are not confident, and their motor development is hampered. The solution taken by the teacher is to provide meaningful material understanding first so that it is easier for children to be more confident and develop their gross motor skills when practicing in the field. Conclusion, Physical education has a significant influence on both aspects. Through structured physical activities, children can improve their gross motor skills, such as walking, running, jumping, and balance skills Keywords: Elementary school children, Motor development, Physical education, Self-confidence,